In vitro reduction of colistin susceptibility and comparative genomics reveals multiple differences between MCR-positive and MCR-negative colistin-resistant Escherichia coli - Luo Q; Niu T; Wang Y; Yin J; Wan F; Yao M; Lu H; Xiao Y; Li L (Infection and Drug Resistance, 2019)
Qixia Luo,1,* Tianshui Niu,1,* Yuan Wang,1 Jianhua Yin,2 Fen Wan,3 Mingfei Yao,1 Haifeng Lu,1 Yonghong Xiao,1 Lanjuan Li11State Key Laboratory for Diagnosis and Treatment of Infectious Diseases, Hangzhou, The First Affiliated Hospital, College of Medicine, Zhejiang University, People’s Republic of China; 2College of Biotechnology and Bioengineering, Zhejiang University of Technology, Hangzhou, People’s Republic of China; 3College of Laboratory Medicine, Hangzhou Medical College, Hangzhou, People’s Republic of China*These authors contributed equally to this work Objectives: Although resistance to colistin is increasingly reported from clinical settings, the genetic mechanisms that lead to colistin resistance in Escherichia coli have not been fully characterized. Here, we assess the evolution of colistin resistance in clinical isolates of mobilized colistin resistance (MCR)-negative and MCR-positive Escherichia coli.Methods: Spontaneously mutated colistin-resistant progeny were evolved using a step-wise reduction of colistin susceptibility. Resistance phenotypes were confirmed by minimum inhibitory concentration (MIC) determination, and the probable resistance mechanisms were investigated using PCR and reverse transcription-quantitative PCR. Mutated genes of the laboratory-evolved mutants were identified by whole-genome sequencing and comparative genomics. Fitness costs and serum resistance of the mutants were also compared to the corresponding wild types.Results: MCR-negative isolates displayed higher increases in MICs than did MCR-positive isolates following colistin exposure. Upregulation of pmrAB and associated genes was evident among MCR-negative isolates but not MCR-positive isolates. Comparative genomic analysis of mutants and their corresponding wild-types (WTs) revealed numerous mutations in genes encoding membrane transporters and two-component systems. Additionally, MCR-negative mutants exhibited higher fitness costs than MCR-positive mutants compared with their corresponding WTs but displayed similar serum resistance.Conclusion: Our findings reveal multiple differences between MCR-positive and MCR-negative E. coli strains following colistin exposure, which provide reference values for clinical medication.Keywords: colistin resistance, MCR, comparative genomic, Escherichia coli